BROKEN HEART SYNDROME (TAKOTSUBO) - WHEN EMOTIONAL STRESS AFFECTS THE HEART (CIPEEX, 2025)
Introduction: Broken Heart Syndrome, or Takotsubo cardiomyopathy, is an acute and reversible cardiac condition that mimics a myocardial infarction without significant coronary obstruction. It can be triggered by significant emotional stress, such as the loss of a significant loved one, significant conflicts, or an adverse event. Objective: To demonstrate a relation between emotional stress and the cardiac changes characteristic of Takotsubo syndrome. Methodology: The systematic review was conducted using the PICo strategy. PubMed, Scielo, and Google Scholar databases were used, using the Health Science Descriptors, in English, "Takotsubo Cardiomyopathy", "Psychological Stress", and "Cardiomyopathies"; using the Borlean operator AND. Three articles published in the last 5 years and available in full online were selected. Results: After analyzing the studies, it was possible to observe that immediate and unexpected emotional changes cause a large release of catecholamines, causing temporary left ventricular dysfunction, which manifests as chest pain, dyspnea, and electrocardiographic changes similar to a heart attack,in addition to echocardiography showing apical dyskinesia and basal hyperkinesia. In this context, postmenopausal women are more susceptible to developing Broken Heart Syndrome due to considerable factors such as altered autonomic regulation, psychosocial factors, and estrogen deficiency. Although most cases are reversible, serious complications can occur, includingcongestive heart failure, ventricular arrhythmias, cardiogenic shock, and stroke. Conclusions: Takotsubo syndrome highlights the direct impact of emotional stress on the heart, highlighting the importance of recognizing its signs early to prevent serious complications. Interventions such as physical exercise and cognitive-behavioral therapy promote ventricular recovery,increase functional capacity, and reduce complications, reinforcing the importance of integrating mental and cardiovascular health.